2021
DOI: 10.1016/j.pediatrneurol.2020.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Leptomeningeal Capillary Malformation is Associated With Severity of Epilepsy in Sturge-Weber Syndrome

Abstract: Background: Individuals with Sturge-Weber syndrome (SWS) often expereince intractable epilepsy and cognitive decline. We hypothesized that the extent of the leptomeningeal capillary malformation (LCM) may correlate with the severity of neurological impairment due to SWS. We tested the hypothesis in a cross-sectional study of seizure severity and electroencephalographic (EEG) findings and a retrospective cohort study for surgical indications related to the extent of the LCM. Methods: We enrolled 112 patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Model estimates suggested that standard postsymptomatically treated patients were 9.24 times more likely to have seizure onset by 2 years (p < 0.001, 95% CI: 2.74-31. 19). In this regression model, females were 3.67 times more likely to have seizure onset by 2 years (p = 0.029, 95% CI: 1.139-11.834).…”
Section: Presymptomatic Treatmentsmentioning
confidence: 75%
See 2 more Smart Citations
“…Model estimates suggested that standard postsymptomatically treated patients were 9.24 times more likely to have seizure onset by 2 years (p < 0.001, 95% CI: 2.74-31. 19). In this regression model, females were 3.67 times more likely to have seizure onset by 2 years (p = 0.029, 95% CI: 1.139-11.834).…”
Section: Presymptomatic Treatmentsmentioning
confidence: 75%
“…18 A greater extent of brain involvement has been associated with an earlier age of seizure onset and worse seizure severity. [16][17][18][19][20] Early seizure onset has been associated with lower IQ, increased hemiparesis severity, increased seizure activity, worse brain injury, and cognitive decline. 13,[21][22][23][24][25][26] In a study of 33 young children with SWS, lower IQ was associated with younger age of seizure onset.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is imperative to manage and control seizures early on to prevent cognitive setbacks. [ 10 , 11 ]. SWS patients rarely have intracranial hemorrhages, and there is little evidence of acute cerebral ischemia [ 12 ].…”
Section: Introductionmentioning
confidence: 99%